2022
DOI: 10.1002/cncr.34356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity and white adipose tissue inflammation on the omental microenvironment in endometrial cancer

Abstract: Background A complex relationship between adipose tissue and malignancy, involving an inflammatory response, has been reported. The goal of this work was to assess the prevalence of white adipose tissue (WAT) inflammation in patients with endometrial cancer (EC), and the association with circulating inflammation markers. Furthermore, the aim was to characterize the pathways activated in and the cell type composition of adipose tissue in patients with EC. Methods Adipose tissue and blood samples were prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Antibodies targeting the IL6 receptor and small-molecular inhibitors of JAK1 and STAT3 have been shown to inhibit endometrial cancer growth both in vitro in cell lines and in vivo in mice (41). The published literature also provides clues potentially implicating the obesity-driven pro-inflammatory interferon response in endometrial cancer pathogenesis, and in keeping with this we found that the other top ranked pathways significantly upregulated with higher genetic BMI in our analyses included the inflammatory response and interferon-gamma and -alpha pathways (42, 43).…”
Section: Discussionsupporting
confidence: 86%
“…Antibodies targeting the IL6 receptor and small-molecular inhibitors of JAK1 and STAT3 have been shown to inhibit endometrial cancer growth both in vitro in cell lines and in vivo in mice (41). The published literature also provides clues potentially implicating the obesity-driven pro-inflammatory interferon response in endometrial cancer pathogenesis, and in keeping with this we found that the other top ranked pathways significantly upregulated with higher genetic BMI in our analyses included the inflammatory response and interferon-gamma and -alpha pathways (42, 43).…”
Section: Discussionsupporting
confidence: 86%
“…Adipose tissue is categorized into two subtypes, white adipose tissue (WAT) and brown adipose tissue. WAT is the main form of fat storage in the body, while brown adipose tissue primarily plays a role in thermogenesis ( Moukarzel et al, 2022 ). Studies have shown that when WAT turns brown, cancer patients develop cachexia, and fat cells are reshaped.…”
Section: Lipid Metabolism and Tumour Growthmentioning
confidence: 99%
“…Adipocytes produce adipocytokines and adipokines, which are essential for tumour angiogenesis. They stimulate tumour cells and mediate their proliferation and migration to promote tumour progression ( Rathmell, 2021 ; Moukarzel et al, 2022 ).…”
Section: Lipid Metabolism and Tumour Growthmentioning
confidence: 99%
“…White adipose tissue (WAT), the most abundant adipose form, secretes numerous adipokines and cytokines to regulate whole-body metabolism. Moreover, WAT inflammation, which increases the expression of proinflammatory and proneoplastic genes, is associated with endometrial cancer ( Moukarzel et al, 2022 ). Additionally, it has become helpful to evaluate biomarkers in relation to cancer risk ( Linkov et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the endometrial cancer incidence rate is approximately 7.74/100 000, and the mortality rate is approximately 1.60/100 000 ( Sun et al, 2022 ). The increasing mortality rates are mainly associated with the increasing incidence of obesity, a leading cause of endometrial cancer ( Ding et al, 2020 ; Larsson.et al, 2022 ; Moukarzel et al, 2022 ). In adjusted mixed linear models, weight loss is strongly related to the levels of cancer-associated biologically active substances, including reduced interleukin-6 (IL-6) levels and increased adiponectin levels ( Linkov et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%